Effectiveness of Physical Activity Interventions on Preventing Gestational Diabetes Mellitus and Excessive Maternal Weight Gain: A Meta-Analysis - Garcia-Hermoso, A (2015)
Background It is commonly accepted that pregnancy-related physiological changes (circulatory, respiratory, and locomotor) negatively influence the daily physical activity of pregnant women. Objectives The aim of this study is to conduct a meta-analysis of randomised controlled trials (RCTs) for assessing the effectiveness of physical exercise interventions during pregnancy to prevent gestational diabetes mellitus and excessive maternal weight gain. Search strategy Keywords were used to conduct a computerised search in six databases: Cochrane Library Plus, Science Direct, EMBASE, PubMed, Web of Science, and ClinicalTrials.gov. Selection criteria Healthy pregnant women who were sedentary or had low levels of physical activity were selected for RCTs that included an exercise programme. Data collection and analysis Two independent reviewers extracted data and assessed the quality of the included studies. Of 4225 articles retrieved, 13 RCTs (2873 pregnant women) met the inclusion criteria. Pooled relative risk (RR) or weighted mean differences (WMDs) (depending on the outcome measure) were calculated using a random-effects model. Main results Overall, physical exercise programmes during pregnancy decreased the risk of gestational diabetes mellitus (RR = 0.69; P = 0.009), particularly when the exercise programme was performed throughout pregnancy (RR = 0.64; P = 0.038). Furthermore, decreases were also observed in maternal weight (WMD = -1.14 kg; 95% CI -1.50 to -0.78; P < 0.001). No serious adverse effects were reported. Conclusion Structured moderate physical exercise programmes during pregnancy decrease the risk of gestational diabetes mellitus and diminish maternal weight gain, and seem to be safe for the mother and the neonate; however, further studies are needed to establish recommendations. Tweetable abstract Exercise programmes decreased the risk of gestational diabetes mellitus and excessive weight gain. © 2015 Royal College of Obstetricians and Gynaecologists.
Keywords: Exercise; gestational diabetes mellitus; maternal weight gain; physical activity; pregnancy